1987
DOI: 10.1139/z87-076
|View full text |Cite
|
Sign up to set email alerts
|

Effect of petroleum hydrocarbons on Atlantic cod, Gadus morhua, following chronic exposure

Abstract: Experiments were conducted to ascertain the effects of crude oils at low concentrations on Atlantic cod (Gadus morhua) following long-term exposure (3–21 weeks) in a flow-through seawater system. Control and oil-treated fish were fed to satiation. Effects were assessed by comparing condition factor, organ indices, and hematological values with those of corresponding control animals. No mortality occurred but food consumption was significantly reduced in oil-treated cod, especially during summer–autumn. Conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 15 publications
3
25
0
Order By: Relevance
“…Rypel and Bayne (2010) evaluated growth rates of six fish species correlated with PCB concentrations in a moderatelyto-heavily polluted freshwater ecosystem, and concluded that at the range of concentrations investigated, these PCBs do not exert negative impacts on growth. Conversely, decreased CF has been recorded in several disturbed sites, such as, for the Atlantic cod, Gadus morhua Linnaeus, 1758 exposed to petroleum (Kiceniuk & Khan, 1987), for white sucker (C. commersoni) in sites with high concentration of metals Cu and Zn (Munkittrick & Dixon, 1988;Miller, Munkittrick & Dixon,1992). In accordance with Liebel et al (2013), CF is an indicative of the health status and may be used to assess field contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Rypel and Bayne (2010) evaluated growth rates of six fish species correlated with PCB concentrations in a moderatelyto-heavily polluted freshwater ecosystem, and concluded that at the range of concentrations investigated, these PCBs do not exert negative impacts on growth. Conversely, decreased CF has been recorded in several disturbed sites, such as, for the Atlantic cod, Gadus morhua Linnaeus, 1758 exposed to petroleum (Kiceniuk & Khan, 1987), for white sucker (C. commersoni) in sites with high concentration of metals Cu and Zn (Munkittrick & Dixon, 1988;Miller, Munkittrick & Dixon,1992). In accordance with Liebel et al (2013), CF is an indicative of the health status and may be used to assess field contamination.…”
Section: Discussionmentioning
confidence: 99%
“…The number of fish of each sex exposed and duration of each experiment are shown in Tables 2 and 3. The method of preparation of the WAFs was described previously (Kiceniuk & Khan, 1987). Two hundred ml of Hibernia crude oil originating from the continental shelf from offshore Newfoundland, were placed each week in a 80L head tank supplied with a 2-volt motor stirrer to ensure mixing with a constant inflow, 2L/min, of seawater.…”
Section: Methodsmentioning
confidence: 99%
“…Two hundred ml of Hibernia crude oil originating from the continental shelf from offshore Newfoundland, were placed each week in a 80L head tank supplied with a 2-volt motor stirrer to ensure mixing with a constant inflow, 2L/min, of seawater. This protocol, identical to previous studies, administered 200 ml of crude oil weekly to the head tank (Kiceniuk & Khan, 1987). The WAFs were drawn off from the bottom of the head tank into the aquarium housing the experimental group.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations